Hubungan Pengetahuan dan Dukungan Tempat Kerja dengan Pemberian ASI Eksklusif pada Ibu Bekerja - Famelya Syafrilina; Delima Delima; Elvia Metti; Lola Felnanda Amri; Tisnawati Tisnawati (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2023)
Exclusive breastfeeding is very important for child growth and development. But there are several factors that inhibite it, such as mother’s knowledge and lack of workplace support. The Padang city has not reached yet the government’s exclusive breastfeeding target. This study aims to determine the relationship between knowledge and workplace support in exclusive breastfeeding for working mothers in Nanggalo District.This is a quantitative with a cross sectional study design. The study was conducted in Nanggalo District in January-June 2022. The population was working mothers who had children aged 6-24 months with a total sampling technique of 30 mothers. Instrument used is a questionnaire with the chi-square statistical test. The results showed that there was no relationship between maternal knowledge (p-value = 0.272) and workplace support (p-value = 0.940) with exclusive breastfeeding.This still needs to increase mother’s knowledge by not providing additional drinks or food and the need for workplace support to increase exclusive breastfeeding.